Heart rhythm assessment in elite endurance athletes: A better method? - Ausland, Ådne; Sandberg, Edvard Liljedahl; Jortveit, Jarle; Seiler, Stephen (Frontiers in Sports and Active Living, 2022)
ABSTRACT INTRODUCTION: Arrhythmias also occur among elite endurance athletes. Conventional diagnostic tools for assessment of arrhythmias suffer from limited availability and usability challenges, particularly under the demanding training conditions of an elite athlete. Among endurance athletes, there is a need for out-of-hospital monitoring to enhance detection of arrhythmias under conditions that are relevant and potentially provocative of underlying pathology. The Norwegian patch ECG247 Smart Heart Sensor has been developed to simplify the assessment of heart rhythm disorders. The current study aimed to evaluate the ECG247 Smart Heart Sensor function and usability in an elite athlete environment. METHODS: A total of 13 professional cyclists from the UNO-X Pro Cycling Team were examined with the ECG247 Smart Heart Sensor during training camp in Spain, December 2021. All ECG data were analyzed by cardiologists at Sorlandet Hospital Arendal, Norway. The athletes also completed a brief questionnaire registering their training (from on-bike monitoring units) and provided self-assessment of usability parameters after the test. RESULTS: In 8 of 13 athletes (69% male, age 234 years), two test periods were performed with different ECG patches, resulting in a total of 21 tests with continuous ECG monitoring. Average total ECG test duration per athlete was 14447 hours (8924hours/patch). Athletes performed an average of 155 training hours during each test. The ECG quality from all tests was considered satisfactory for rhythm analysis – also during exercise. The reported usability of the ECG247 Smart Heart Sensor was high, and no athletes reported trouble sleeping or training with the sensor. The automatic arrhythmia algorithm reported episodes of possible arrhythmias in 5 (24%) tests; 2 atrial flutter, 2 supraventricular tachycardia and 1 bradycardia (heart rate < 30/min). Manual assessment by physicians verified the episode of bradycardia but revealed normal sinus rhythm in all other tests. No false negative events were identified in over 1800 hours of ECG collection. CONCLUSION: The ECG247 Smart Heart Sensor allowed for high quality ECG monitoring with high usability during intensive exercise in athletes.